On Mixed Quermassintegral for Log-Concave Functions. (17th November 2020) - Chen, Fangwei; Fang, Jianbo; Luo, Miao; Yang, Congli
Abstract : In this paper, the functional Quermassintegral of log-concave functions in ℝ n is discussed. We obtain the integral expression of the i th functional mixed Quermassintegral, which is similar to the integral expression of the i th mixed Quermassintegral of convex bodies.